Influence of electronic and formulation variables on transdermal iontophoresis of tacrine hydrochloride. (June 2015) - Patel, Niketkumar; Jain, Shashank; Madan, Parshotam; Lin, Senshang
Abstract Freshly excised rat skin and side-by-side permeation cells were used to study the effect of electronic and formulation variables on transdermal iontophoretic delivery of tacrine. Current strength at 0.1–0.3 mA was observed to be the driving force resulting in tacrine permation flux of 30.3–366.6 μg/cm2/h. Depot formation of tacrine and altered skin permeability resulted in post iontophoretic flux even after termination of applied current. Increase in the duration of current application did not show significant difference in tacrine permeation flux upto 6 h. Tacrine permeation was directly proportional to tacrine concentration upto 10 mg/ml but further increase in concentration (upto 20 mg/ml) exhibited permeation flux plateau. Buffer molarity had an inverse relationship on permeation flux and the presence of co-ions in formulation exhibited reduced permeation flux. Permeation flux decreased when pH of formulation was successively increased from 7.0 to 10.0 suggesting electromigration of tacrine. Alternate buffer systems including HEPES and Tris showed improved tacrine permeation due to their larger ion size compared to phosphate buffer ions. The results of this study show that transdermal tacrine permeation can be controlled by electronic and formulation variables which would be useful for the development of transdermal iontophoretic delivery of tacrine for the treatment of Alzehimer's disease.